Analysis of the Influence of Poverty Levels in Tuban District - Rochimin, Reinanda Aprilia Putri; Huda, Syamsul; Perdana, Putra (PT Inovasi Pratama Internasional, 2024)
This study aims to determine the relationship between population size, economic growth, education level, and unemployment rate on the poverty level in Tuban Regency. Tuban Regency is a district with a poverty percentage reaching 14.91% in 2022. The researchers used a quantitative approach with multiple linear regression analysis. The results show that the population size has a positive effect on the poverty level, economic growth has a negative effect on the poverty level, the education level has a positive effect on the poverty level, and the unemployment rate has a positive effect on the poverty level in Tuban Regency. The data used in this study include secondary data obtained from the Central Statistics Agency and other related sources. This research provides significant contributions to understanding the factors influencing poverty in the area, which can serve as a basis for policy formulation to reduce poverty. Potential policies include improving the quality of education, creating new job opportunities, and promoting inclusive economic growth. Improving the quality of education is expected to enhance the skills and competitiveness of the workforce, while the creation of new jobs can reduce the unemployment rate. Inclusive economic growth ensures that the benefits of economic growth are felt by all layers of society, particularly the poor. Therefore, this study offers comprehensive insights into the relationship between these variables and provides policy recommendations that can help reduce the poverty rate in Tuban Regency.